Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1097/01.sap.0000134342.04860.99
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Blood Transfusion in TRAM Breast Reconstruction:

Abstract: Many centers continue to use preoperative donation of autologous blood as part of their reconstructive protocol for pedicled transverse rectus abdominis musculocutaneous (TRAM) breast reconstruction, despite the lack of support for this in the English language literature. This prospective study compares 3 groups of patients undergoing reconstruction with TRAM flaps using 3 different protocols in 3 different centers. Group 1 did not donate blood preoperatively. Group 2 donated 1 to 2 U preoperatively and receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Smith et al 7 also showed that the complication rates (11%) and blood transfusion rates (9%) were low. The complication rate for the contralateral breast was extremely low (1%), although previous studies have shown a desire to perform these procedures simultaneously because the risk of blood loss causes an unacceptably high rate of blood transfusion [14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al 7 also showed that the complication rates (11%) and blood transfusion rates (9%) were low. The complication rate for the contralateral breast was extremely low (1%), although previous studies have shown a desire to perform these procedures simultaneously because the risk of blood loss causes an unacceptably high rate of blood transfusion [14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Low preoperative hemoglobin levels may be attributed to the patient's oncologic state, effects of chemotherapy, nutritional state, and the undertaking of preoperative autologous blood donation. 7,25,28,29 The practice was popularized in the 1990s in the event of reported allogenic blood transfusion-related blood-borne infections. Autologous blood transfusion has also been said to reduce hospital stay, lower complication rate, and enable an earlier return to preoperative level but may increase postoperative transfusion requirements.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a standardized method of measuring blood loss, the incidence, rate, and volume of transfusion have been widely used as an indirect marker of perioperative blood loss. The literature reports a transfusion rate in transverse rectus abdominis myocutaneous (TRAM) flap patients averaging anywhere from 6 to 95%, [3][4][5][6][7][8][9] with Holley et al reporting a transfusion rate of 95% in both pedicled and free TRAM flaps. 10 This broad range reflects the differing policies for transfusion between units and between physicians.…”
mentioning
confidence: 99%
“…A review of the literature indicated that the transfusion rate in TRAM flap patients is 6–95% . Recent studies showed that transfusion is associated with adverse clinical outcomes in free flap surgery .…”
mentioning
confidence: 99%
“…14 A review of the literature indicated that the transfusion rate in TRAM flap patients is 6-95%. [15][16][17] Recent studies showed that transfusion is associated with adverse clinical outcomes in free flap surgery. [18][19][20] However, no study has investigated the effect of transfusing old blood on postoperative complications following TRAM flap surgery.…”
mentioning
confidence: 99%